A Survey on Wellness and Its Predictors Amongst Fiji High School Students - Latileta Odrovakavula; Masoud Mohammadnezhad; Sabiha Khan (Frontiers Media S.A., 2021)
Background: Adolescent population face a number of health concerns which calls for objective and comprehensive assessment of their wellness during their critical development phase. This study aimed to determine adolescent wellness and its predictors amongst adolescents in secondary schools in Fiji.Methods: This quantitative cross sectional study was conducted in four purposively selected schools in Suva and the greater Suva area, Fiji, between August and September, 2019. Students of Fijian nationality, enrolled into years 11-13 in the selected schools were purposively selected. A structured self-administered questionnaire was used to collect data on four dimensions of wellness including physical, emotional, social, and spiritual. Spearman's Rho correlation was conducted to test for associations. Descriptive and inferential statistical tests were applied to analyze the data by the SPSS software version 25. A p-value < 0.05 was considered significant.Results: A total of 350 students participated in the study. Mean raw scores for wellness dimensions were as follows: physical = 51 (out of 60), psychological = 63 (out of 80), social = 42 (out of 50), and spiritual = 34 (out of 40). For overall wellness, two significant differences were observed: students of Fijian Itaukei descent (193.68 ± 14.2) and participants with a family income of $40,000-50,000 (199.08 ± 12.60) (p = 0.04) had a higher overall wellness score. There were three significant differences observed for psychological wellness dimension; Fijians of Indian descent (64.68 ± 9.30), participants enrolled into year 13 (64.68 ± 9.30) and those with a family income of $40,000-50,000 had higher psychological score. For social wellness, a significant difference was observed: Itaukei participants had higher scores (43.34 ± 4.42) when compared to other ethnic groups (p < 0.05). In terms of spiritual wellness, a significant difference was observed for ethnicity: Itaukei participants had a higher mean score (35.59 ± 4.26) when compared to other ethnic groups (p < 0.05). Strong correlations were observed for all dimensions of wellness.Conclusions: Findings of this study highlighted different factors affecting adolescents' wellness in Fiji. It is recommended that health education and awareness program be carried out for developing adolescent wellness by considering these factors. It is also recommended that parental and family support are provided to adolescents.